The Algorithmic Compass: Charting the Future of AI in Mental Health Treatment - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The global mental health crisis presents a formidable challenge to traditional healthcare systems. With depression alone being the leading cause of disabilit...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation